Photoreduction of Thioether Gold(III) Complexes: Mechanistic Insight and Homogeneous Catalysis. Issue 70 (15th November 2018) - Cao, Zhen; Bassani, Dario M.; Bibal, Brigitte
Abstract: Complexes formed between AuCl3 and thioether ligands underwent a photoinduced reductive elimination under homogeneous conditions in dichloromethane and toluene solutions to afford the corresponding Au I complexes. All the gold(III) complexes were rapidly reduced to the gold(I) chloride complexes under 365 nm irradiation or ambient light while being thermally stable below 55 °C. The mechanism of photoreduction through Cl2 elimination is discussed based on a kinetic study and the chemical trapping of chlorine species: Cl2, radical Cl ., and possibly Cl + . The catalytic activities of the gold(III) chloride complexes and the corresponding gold(I) complexes obtained by in situ reduction were evaluated in the cyclization of N ‐propargylic amides to oxazoles. The merits of such photoreducible complexes in homogeneous gold catalysis are illustrated by a cascade reaction catalyzed by thioether gold complexes that affords a 4 H ‐quinolizin‐4‐one in high yields. Abstract : Photoreducing gold : Four homogeneous dialkyl thioether gold(III) complexes undergo a rapid halogen photoreductive elimination process to the corresponding gold(I) complexes. The catalytic properties of these gold chlorides in different oxidation states were evaluated in the cyclization of propargylamines and in a one‐pot cascade reaction towards a fused heteropolycyclic compound (see scheme).